9(n-1)-(-6n-8)=14n

Simple and best practice solution for 9(n-1)-(-6n-8)=14n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(n-1)-(-6n-8)=14n equation:


Simplifying
9(n + -1) + -1(-6n + -8) = 14n

Reorder the terms:
9(-1 + n) + -1(-6n + -8) = 14n
(-1 * 9 + n * 9) + -1(-6n + -8) = 14n
(-9 + 9n) + -1(-6n + -8) = 14n

Reorder the terms:
-9 + 9n + -1(-8 + -6n) = 14n
-9 + 9n + (-8 * -1 + -6n * -1) = 14n
-9 + 9n + (8 + 6n) = 14n

Reorder the terms:
-9 + 8 + 9n + 6n = 14n

Combine like terms: -9 + 8 = -1
-1 + 9n + 6n = 14n

Combine like terms: 9n + 6n = 15n
-1 + 15n = 14n

Solving
-1 + 15n = 14n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-14n' to each side of the equation.
-1 + 15n + -14n = 14n + -14n

Combine like terms: 15n + -14n = 1n
-1 + 1n = 14n + -14n

Combine like terms: 14n + -14n = 0
-1 + 1n = 0

Add '1' to each side of the equation.
-1 + 1 + 1n = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 1n = 0 + 1
1n = 0 + 1

Combine like terms: 0 + 1 = 1
1n = 1

Divide each side by '1'.
n = 1

Simplifying
n = 1

See similar equations:

| 40h-[24-(6h+8)-(5-2h)]=3-8h-12 | | 4*16/8+8+5-1+4 | | 0.13-0.02(x+1)=-0.03(3-x) | | -6a+42=10a+35 | | 22-13x=9 | | 6x+4-5x=0 | | 5y-23=-25+3y | | 250.00(h+15.00)=412.50 | | -9(-6+x)=-63 | | -6x^5+6x^4-2x^3=0 | | 165g=75 | | 11xy+2x=2 | | 250(h+15)=412.50 | | 85=21+4xs | | -3(3.3+8.9r)=6.1-24.7r | | n/15=1 | | (1-x)100=0.25 | | -4v/7=-20 | | 3(b+5y)=2(-5+4y) | | 5y-29=-31+4y | | 2(x-3)+7=10 | | (5/1)-(2(3a-4)/5)=(7-2a/2) | | -9c+1=-35 | | -7+36/-9x-1 | | 2x^3+5x+2=0 | | 4d-1=-4+4d+3 | | 3*n+4=18+n | | 8x+8=7x+2-1 | | 2(3a-4)= | | -7+36/-9 | | 2x*ln(x)=5 | | 3+4(2u-2)=-2(6u-5)+2u |

Equations solver categories